Innovative Technologies in Countering Extremism and Terrorism - Aftab Ahmad Malik; Waqar Azeem; Mujtaba Asad (International Journal for Electronic Crime Investigation, 2023)
Terrorism and extremism are distinct concepts often interconnected in discussions about political, religious, or ideological violence. Terrorism mentions to the use of vehemence, pressure, or force to attain party-political, spiritual, or conceptual areas, disrupting normal life and exerting pressure on governments or societies. Extremism, characterized by extreme political or religious views, often involves radical ideologies and intolerance towards opposing beliefs, often seeking dramatic changes in society or politics, rejecting moderation. Extremist ideologies can sometimes lead to terrorist acts, but not all extremists resort to violence. It's crucial to differentiate between extreme beliefs and violent actions, as not all terrorists are driven by extremism. Recommendations to safeguard against security threats are proposed.